2020
DOI: 10.1016/j.jad.2020.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of respiratory protective devices on respiration: Implications for panic vulnerability during the COVID-19 pandemic.

Abstract: Highlights Panic-prone individuals often exhibit reduced tolerance when wearing RPDs Studies found that wearing RPDs may induce a real burden of respiratory effects Panic-prone individuals may be at higher risk of RPD-related respiratory discomfort Various strategies to decrease discomfort may overcome the risk of poor compliance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…In claustrophobia, the anxiety is localized leaving the other psycho-behavioral fields free. Respiratory protective devices (RPDs) may cause respiratory discomfort in panic-prone individuals [ 17 ]. Furthermore, anxiety may develop to coronaphobia which is associated with avoidance of public places and events [ 18 , 19 ].…”
Section: Contributory Factors For Psychological Effects Of Covid-19 Pmentioning
confidence: 99%
“…In claustrophobia, the anxiety is localized leaving the other psycho-behavioral fields free. Respiratory protective devices (RPDs) may cause respiratory discomfort in panic-prone individuals [ 17 ]. Furthermore, anxiety may develop to coronaphobia which is associated with avoidance of public places and events [ 18 , 19 ].…”
Section: Contributory Factors For Psychological Effects Of Covid-19 Pmentioning
confidence: 99%
“…A review notably supports the idea that panic-prone individuals may be at higher risk of respiratory discomfort when wearing RPDs, thereby reducing their tolerance for these devices [55].…”
Section: Psychological Effectsmentioning
confidence: 81%
“…It has been observed that despite high efficiency, N95 face masks reduce ventilation, cardiopulmonary exercise capacity, and comfort and lead to dizziness, reduced oxygen supply, and itchiness to wearer [ 41 ]. Studies have shown that wearing N95 or surgical masks has resulted in decrease in VO 2max emission as well as reduced ventilation, due to steady decrease in breathing frequency [ 42 ]. This added breathing resistance in the upper respiratory tract may also lead to disruption in lung functionality as well as increase the risk of cardiac arrest, as the study suggests [ 43 , 44 ].…”
Section: Filtration Of Pms Using Ultrafine Fibersmentioning
confidence: 99%